Brand Preference of Two Wheeler’s: Problems and Satisfaction Level of Consumers - Kannusamy, K. (Ushus Journal of Business Management, 2010)
Transport is an important aid for better hiring. Two — wheelers are becoming more popular especially among the people belonging to middle income group. There are wide choice of brands there is a stiff competition among the manufactures and marketers to attract the attention of buyers. People prefer a specific model of motorcycle among different brands for various reasons like price, maintenance, fuel efficiency appearance, durability and resale value. Today the iwo wheeler industry plays a significant role in the Indian economy. India is the second largest manufactures of two — wheelers in the world. One of the very important characteristics of economic development is the transformation of luxury goods into necessary goods. In recent time one such goods, which has been highly demanded by the customers, is the motor cycle possessing a mechanical devices for conveyance is an indicator of good standard of living. Hence an attempt to be made on the Brand Preference of Two—Wheelers Problems and Satisfaction of consumers.